Analysis of Changes in Oral Microbiota for Interval of Post-Mortem Estimation: Review Article - Langit, Ken Sekar; Prabowo, Yoghi Bagus; Shifa, Liftia Layyinatus (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: The microbiota change caused by the decomposition process after death can be used to determine the post-mortem interval. This condition is associated with changes in the oral microbiota. Oral microbiota can be used as an appropriate source for analysis without interfering with the corpse or breaking Indonesian law. This review will examine the changes in the oral microbiota to determine the time of death. Method: The literature search was carried out using PubMed, ScienceDirect, and Google Scholar, and the results were screened based on the inclusion and exclusion criteria. Result: The discussion was based on six literature reviews that met the criteria and subject matter of this review. Conclusion: The microbiota in the body contributes to the decomposition process after death. This condition allows it to be used as a reference for determining the postmortem interval. These changes, however, cannot be distinguished from the presence of factors such as temperature, pH, humidity, and an anaerobic environment. Consider these factors when analyzing post-mortem intervals using oral microbiota changes.